골반 골종양 환자에서 제3형 내골반골 절제술 후 수술적, 종양학적 결과 - 전대근(Dae-Geun Jeon); 조완형(Wan Hyeong Cho); 송원석(Won Seok Song); 공창배(Chang-Bae Kong); 이승용(Seung Yong Lee); 김범석(Bum Suk Kim) (The journal of the Korean Orthopaedic Association, 2016)
목적: 치골 절제 후 골재건은 불필요하나 부분 혹은 전절제 시 기술적 문제점, 절제범위에 따른 기능적 결과와 절제 후 복벽 재건을위해 인공물을 사용하지 않은 경우 실제로 탈장의 위험이 높아지는지는 불확실하다. 대상 및 방법: 치골 및 좌골부의 골종양으로 제3형 내골반골 절제술을 받은 환자 15명의 진단 및 Enneking 병기, 종양의 위치, 크기, 수술 시간, 출혈량, 절제연, 국소재발, 원격전이, 골 절제 범위에 따른 기능적 결과를 분석하였다. 결과: 연골육종이 9예, 유잉육종 3예, 전이성 암이 2예, 골육종 1예였다. 국소재발은 4예였고 그 중 1예는 폐전이가 있었다. 기능적결과는 평균 26점이었다. 반대측 치골을 포함하여 절제한 4예는 25점, 편측 상하 치골지 혹은 좌골만 절제한 7예는 26점, 상하 치골지 및 좌골 전부를 절제한 4예는 평균 24점이었다. 종양이 치골 결합을 넘어 반대측 치골의 일부를 포함한 2예 중 1예는 요도절제가불가피하였고, 1예는 임신 후 자궁의 하방전위가 발생하여 제왕 절개로 출산하였다. 결론: 제3형 내골반골 절제술 후 골의 절제 범위와 관계없이 비슷한 기능적 결과를 보였고 연부조직 재건을 위해 복벽 보 인강공물을사용하지 않아도 탈장의 위험은 낮았으나 반대측 치골까지 절제한 경우 인공물 사용을 고려하는 것이 좋을 것으로 생된각다. Purpose: It is generally accepted that bony reconstruction after type III (pubic) internal pelvectomy is not necessary. However, technical problems in type III resection, functional outcome according to the extent of resection, and the usefulness of synthetic material to decrease the risk of hernia has not been well addressed. Materials and Methods: Fifteen patients who underwent type III internal pelvectomy were extracted and the pathologic diagnosis, Enneking’s stage, location of tumor and size, operation time, amount of transfusion, surgical margin, local recurrence, distant metastasis, and functional outcomes were analyzed according to the extent of resection. Results: Pathologic diagnosis was chondrosarcoma in 9, Ewing’s sarcoma in 3, metastatic carcinoma in 2, and osteosarcoma in 1 patient. There were 4 patients with local recurrence and one with concomitant lung metastasis. Average Musculoskeletal Tumor Society functional score was 26.7. According to the extent of resection, functional score of 7 cases with unilateral both rami (6) or ischium (1) resection was 26, 4 cases with unilateral both rami and partial contralateral pubic ramus resection was 25, and 4 cases with unilateral both rami including ischium was 24. Two patients had tumor related complication. One patient with a huge intrapelvic tumor aroused at the symphysis pubis showed urethral invasion at presentation, therefore, urethral resection and permanent suprapubic cystostomy was inevitable. The other patient with bilateral pubic ramus involvement by tumor showed caudal displacement of the uterus after pregnancy (4 years after primary resection). She underwent Caesearian section for delivery. Conclusion: Regardless of the extent of pubic bone resection, functional outcome was similar. The risk of abdominal or pelvic organ hernia was minimal even without the use of artificial material for soft tissue reconstruction; however, when the extent of resection crosses the symphysis pubis, selective application of an additional procedure to reinforce the pelvic floor may be considered. KCI Citation Count: 0